PEMANFAATAN SAMPAH PLASTIK JENIS HDPE DAN PET SEBAGAI BAHAN BAKU PEMBUATAN BAHAN BAKAR MINYAK ALTERNATIF MENGGUNAKAN METODE PIROLISIS DENGAN KATALIS ZEOLIT ALAM: Utilization Of HDPE And PET Plastic Waste As Raw Materials For Manufacturing Alternative Fuel Using Pyrolysis Method With Natural Zeolite Catalyst - Wahyu Kartika (Universitas Darussalam Gontor, 2022)
Plastic waste is still a serious environmental problem, along with economic growth and increasing population. Plastic is an inorganic material that is difficult to decompose naturally, so alternative processing is needed to reduce the volume of plastic waste. One way is to use plastic waste as a raw material for making alternative fuel oil with the pyrolysis method. This can be done because plastic is a derivative product of petroleum so it has a high calorific value like existing commercial fuels. Pyrolysis is the process of fracturing or breaking polymer chains into simpler compounds through a thermal process with, without or with little oxygen. The purpose of this study was to determine the composition of raw material weight, catalyst weight, temperature and optimal reaction time in the manufacture of alternative fuel oil from a mixture of HDPE and PET plastic waste using the pyrolysis method with the help of a natural zeolite catalyst and its quality according standards lto oil and gas. The results showed that the quality of pyrolysis oil with an optimal composition of weight of raw materials for plastic waste HDPE and PET 500 g, natural zeolite catalyst 200 g, temperature 4000C and reaction time of 30 minutes was included in the standard range of diesel oil according to iDecree and Director General Gas No. 28.K/10/DJM. T/2016, with laboratory test results for viscosity parameters 3.02 mm2/s, density 851.2 kg/m3, heating value 10,228.8 kcal/kg, boiling point 2150C and water content 288 mg/kg.